Cognitive predictors of parent-rated inattention in very preterm children: The role of working memory and processing speed. Issue 5 (4th July 2019) - Retzler, Jenny; Johnson, Samantha; Groom, Madeleine; Hollis, Chris; Budge, Helen; Cragg, Lucy
ABSTRACT: Inattention is one of the most common neurobehavioral problems following very preterm birth. Attention problems can persist into adulthood and are associated with negative socio-emotional and educational outcomes. This study aimed to determine whether the cognitive processes associated with inattention differ between term-born and very preterm children. Sixty-five children born very preterm (<33+0 weeks' gestation) aged 8–11 years were recruited alongside 48 term-born controls (?37 20 +0 weeks' gestation). Both groups included children with a wide spectrum of parent-rated inattention (above average attention to severe inattention) measured as a continuous dimension using the Strengths and Weaknesses of ADHD and Normal-Behavior (SWAN) scale. The children completed tests to assess basic cognitive processes and executive function. A hierarchical multiple regression analysis was implemented to assess which neurocognitive processes explained variance in parent-rated inattention and whether these differed between preterm and term-born children. In both groups, poorer verbal and visuospatial short-term memory and poorer visuospatial working memory independently explained variance in parent-rated inattention. Slower motor processing speed explained variance in inattention among very preterm children only. The cognitive mechanisms associated with parent-rated inattention were predominantly overlapping between groups, but relationships between motor processing speed and inattention were unique to very preterm children. These associations may reflect risk factors for inattention in term and very preterm children. Future research should assess the efficacy of these cognitive processes as potential targets for intervention